Esophageal intramural pseudodiverticulosis in a patient with food bolus impaction - Piñerúa-Gonsálvez, Jean Félix (2020)
Esophageal intramural pseudodiverticulosis is an uncommon esophageal benign disease. The typical finding during endoscopy is the presence of numerous pinhead-sized outpouchings along the esophageal wall. We reported a case of food bolus impaction secondary to esophageal intramural pseudodiverticulosis. A 67-year-old man presented with sudden-onset dysphagia. Multiple tiny orifices were revealed during upper endoscopy. In addition, there were an impacted food bolus and an esophageal web.The patient was treated with balloon dilatation and proton pump inhibitors. As a result the symptoms disappeared completely. Esophageal intramural pseudodiverticulosis is a rare cause of food bolus impaction and its treatment is directed towards the underlying associated conditions as well as the resolution of complications.